Defining the hidden evidence in autism research: forty per cent of rigorously designed clinical trials remain unpublished$da cross-sectional analysis - Mechler, Konstantin; Hoffmann, Georg F.; Dittmann, Ralf; Ries, Markus (International journal of methods in psychiatric research, 2017)
Autism spectrum disorders (ASD) have a prevalence of up to 2.7% and show significant rates of comorbidities. Pharmacological treatment can be difficult. New treatment options are needed, several are currently under investigation. Publication bias presents a major problem in current clinical research. This study was designed to quantify publication bias in rigorously designed ASD research. The database at ClinicalTrials.gov was searched for all completed randomized controlled clinical trials investigating interventions in ASD and their results made public. If results could neither be retrieved through search of the database, nor of scientific databases nor by enquiries of the responsible parties or sponsors listed, a trial was defined as not published. The search delivered N = 30 (60%) trials were published, N = 20 (40%) remained unpublished, N = 2,421 (59%) patients were enrolled in the published trials, N = 1,664 (41%) patients in the unpublished trials, time to publication was 21.4 months [standard deviation (SD) = 18.48; range = −5 to 80 months]. Results of N = 22 trials were available through ClinicalTrials.gov. Characteristics of published compared to unpublished trials did not show apparent differences. The majority of trials investigated drugs. The results emphasize the serious issue of publication bias. The large proportion of unpublished results precludes valuable information and has the potential to distort evidence for treatment approaches in ASD.